2021
DOI: 10.1186/s12917-021-02962-2
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit haemorrhagic disease virus Lagovirus europaeus/GI.1d strain: genome sequencing, in vivo virus replication kinetics, and viral dose effect

Abstract: Background Rabbit haemorrhagic disease virus Lagovirus europaeus/GI.1d variant (GI.1d/RHDV) was identified in 1990 in France, and until the emergence of the new genotype GI.2, it was the main variant circulating in the country. The early stages of RHDV infection have been described in a few studies of rabbits experimentally infected with earlier strains, but no information was given on the minimum infective dose. We report the genomic and phenotypic characterisation of a GI.1d/RHDV strain colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The RT-qPCR method used in this study is a highly sensitive method that detects minimum amounts of GI.2 viral RNA [ 41 ]. Previously, Gehrmann and Kretzschmar [ 22 ] found that 10–100 virus particles were the minimum dose required to induce disease in rabbits; a more recent study showed that the minimum infective dose for GI.1 is ≤ 10 4 gRNA copies [ 50 ]. However, this has not been fully assessed for GI.2.…”
Section: Resultsmentioning
confidence: 99%
“…The RT-qPCR method used in this study is a highly sensitive method that detects minimum amounts of GI.2 viral RNA [ 41 ]. Previously, Gehrmann and Kretzschmar [ 22 ] found that 10–100 virus particles were the minimum dose required to induce disease in rabbits; a more recent study showed that the minimum infective dose for GI.1 is ≤ 10 4 gRNA copies [ 50 ]. However, this has not been fully assessed for GI.2.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the bibliography ( 35 39 ), we hypothesize that the level of specific serum IgG, achieved after seroconversion to MYXV or RHDV GI.2, might be associated with the interaction between the doses of virus to which individual rabbits are exposed (inoculum) and the individual immune competence. The infective dose of RHDV GI.2 was shown to be <10 4 viral genomes, but >10 7 genome copies was required to cause mortality ( 40 ). This highlights a large span of infective doses (10 4 to 10 7 ) that could infect and subsequently immunize rabbits while not causing mortality.…”
Section: Discussionmentioning
confidence: 99%